The Characteristics of Shalihah Woman in the Qur’an: Quraish Shihab’s Perspective in Tafsir Al-Mishbah - Shery Fara Afifah; Nasrulloh (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The study of the characteristics of shalihah women is very important to study. Islam positions women as very noble, valuable and dignified creatures. Shalihah women have a big impact, especially in educating and forming the next generation. A mother has an important role in guiding and educating her children. So if the mother is good, it is likely that her children will also grow up to be good individuals. This makes an extraordinary contribution to the formation of a better and civilized society. The research uses qualitative research and Library Research as type of the research. Primary data sources were taken from Tafsir Al-Mishbah and secondary data from books, journals and related articles. Data analysis in this study used descriptive-deductive. The researcher will describe the verses that related to the characteristics of shalihah women in the Qur'an in general and then specifically based on the Quraish Shihab’s perspective in Tafsir Al-Mishbah. The aim of this research is to determine the characteristics of pious women in the Qur'an based on the Quraish Shihab’s perspective in Tafsir Al-Mishbah. The results of this research are the importance of moral perfection, piety, obedience and loyalty to the teachings of the Islamic religion. Specifically are covering one's private parts properly, including holding up the hijab, obeying Allah and her husband, maintaining chastity and honor, guarding one's genitals, patience, khusyu' and qunut, which includes all types of obligatory and sunnah obedience.